Analisa Hubungan Kepuasan Kerja dengan Loyalitas Karyawan di PT CAR - , Syefi Noverine ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research aims at analyzing the relationship of job satisfaction towards employee loyalty in PT CAR, and which aspects of the nine job satisfaction aspectsinfluence significantly to employee loyalty. The nine aspects of job satisfaction which are used in this research are: salary, promotion, supervision, fringe benefits, contingent reward, condition of the company, co-workers, nature of work, and communication. Primary and secondary data are used in this research, by distribution of questionnaires to all operational employees within the organization as the source of primary data.Internal company data and literature review are the sources of secondary data. Total subject was 198 people taken from 392 people by Proportional Random Sampling approach. Pearson Product Moment correlation was utilized to examine the correlation between job satisfaction and employee loyalty. Multiple regression analysis was employed to examine the relationship between dependant variable and two or more independent variables. The correlation analysis result showed that r = 0,267